If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(x + -1) = -2x + -1(x + 4) Reorder the terms: -2(-1 + x) = -2x + -1(x + 4) (-1 * -2 + x * -2) = -2x + -1(x + 4) (2 + -2x) = -2x + -1(x + 4) Reorder the terms: 2 + -2x = -2x + -1(4 + x) 2 + -2x = -2x + (4 * -1 + x * -1) 2 + -2x = -2x + (-4 + -1x) Reorder the terms: 2 + -2x = -4 + -2x + -1x Combine like terms: -2x + -1x = -3x 2 + -2x = -4 + -3x Solving 2 + -2x = -4 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. 2 + -2x + 3x = -4 + -3x + 3x Combine like terms: -2x + 3x = 1x 2 + 1x = -4 + -3x + 3x Combine like terms: -3x + 3x = 0 2 + 1x = -4 + 0 2 + 1x = -4 Add '-2' to each side of the equation. 2 + -2 + 1x = -4 + -2 Combine like terms: 2 + -2 = 0 0 + 1x = -4 + -2 1x = -4 + -2 Combine like terms: -4 + -2 = -6 1x = -6 Divide each side by '1'. x = -6 Simplifying x = -6
| 9x-11-2x+4= | | x^2+y^2-12y=0 | | 2-10=z/-7 | | 3x-5y+4y+2x= | | 14x^2-24=0 | | 0=X^4-8x | | y-.333=2.66 | | -3(x-2)+4(x-7)=20 | | u+.333=.333 | | 4x+4(6x+3)= | | -0.55p-5=0.45 | | cosx/2-1=0 | | 7x^4+2x^2+21=0 | | -4-(2y-1)=-(3y+1) | | 21/4=8/t | | 4*(x+6)= | | X(-2)+18=50(-3x)+25 | | 2*(x+3)= | | 2*(3a)= | | -24+x=36 | | (-2x)+5+3x+-4x+(-1)+(-x)= | | 2x+(-2)=17 | | 6*2s=39 | | ×/3-4=×/5-6 | | 2(-1)+y=17 | | Y+12=c | | 3/7=n/21 | | 4.5+x=-2.3 | | 10x-15=6x+14 | | 3(7+2x)=7(x-1) | | ln(5-x)=2.3 | | 7m-2t=72 |